Clothing and grooming practices of Home Economics students and their implications for the college clothing course - Uytingco, Milagros (Santos) 1934- (1961)
This study is an exploratory approach to a better understanding of the girls' behavior with respect to their clothes and appearance with the purpose of gaining insights into their clothing and appearance behavior. An attempt has been made in this study to gather some factual information regarding clothing and grooming practices of home economics students in the University of the Philippines. The investigator inquired into certain factors in the students background such as age, family, economic level and social participation in campus activities which may have a bearing on the extent of their clothing and appearance behavior. The results of the study show that the girls' clothing and grooming behavior regardless of age, family economic level and their social campus participation are well manifested in the upkeep of their appearance in their clothing practices particularly those in the selection, purchase and care of clothing. The results of this study are discussed in the manuscript and clothing practices particularly those in the selection, purchase and care of clothing. The results of this study are discussed in the manuscript and presented in the tables and figures. The general findings suggest that clothing courses geared to meet the needs of the students should be more of the functional type and not only acquainting them with the theoretical foundations of clothing and appearance. This study hopes to serve as a basis for suggested class activities which may be included in the teaching of the basic college clothing course.